Inter‐ and intra‐operator variability in the analysis of packed cell volume. (24th November 2016) - Breheny, C. R.; Brown, A.; Handel, I.; Gow, A. G.
Abstract : Objectives: To identify whether inter‐ and intra‐operator variability occurs in the measurement of canine packed cell volume and, if so, at which stage these errors occur. Materials and Methods: Undergraduate veterinary students and veterinary surgeons were recruited to measure the packed cell volumes of three samples in duplicate. Measurements from each sample were confirmed by one author, and it was then ascertained whether the error was made in the capillary preparation or reading. Results: Data were obtained from 44 students and 11 vets. A total of 25% of students made errors associated with inadequate mixing; 23% students and 9% of vets made errors consistent with incorrect reading. There was also less intra‐operator variation in values within the vet group (0·027 from the mean) in comparison to the student group (−0·21 from the mean). A total of 68·2% of students and 91% of vets filled the capillary tubes outwith World Health Organisation standards of two‐thirds to three‐quarters full. Clinical Significance: Packed cell volume measurement is extremely useful when measuring erythroid mass, but it is crucial that the results upon which decisions are made are accurate and precise in order to manage these cases appropriately. Operator variation is a significant factor and must be addressed by proper training and following standard operating procedures.